Cyberstalking Victims’ Experiences With Fear Versus Other Emotional Responses to Repeated Online Pursuit: Revisiting the Fear Standard Among a National Sample of Young Adults - Fissel, Erica R. (Crime & delinquency, 2024)
This study empirically examines situational and personal characteristics associated with victims? responses to cyberstalking. In the context of these responses, there has been much debate regarding the ?fear standard,? which requires victims or reasonable persons to feel fearful as a result of stalking. To examine victim responses to cyberstalking, survey data were collected from 880 young adults in the U.S. who were repeatedly pursued online (cyberstalked) within the previous year. Findings revealed that the majority (67.84%) of respondents did not feel fear in response to the repeated online pursuit. However, approximately half (50.23%) did experience a substantial (non-fear) emotional response. Multivariate findings identified situational and victim characteristics that impacted the reactions experienced, and these effects varied by type of reaction. The results indicate that definitions requiring fear underestimate the prevalence of cyberstalking.